OLIY TA’LIMDA TALABALAR BILIMINI BAHOLAShDA SUN’IY INTELLEKT VA KOGNITIV YONDAShUVLARNING INTEGRATSIYASI - Bazarbaeva, A.K. (SCIENCE and SOCIETY, 2025)
The article examines modern approaches to assessing students’ knowledge in higher education, with a particular focus on the use of artificial intelligence technologies. The role of AI algorithms in ensuring objectivity in assessment, developing students’ cognitive styles, enhancing independent learning, and creating personalized learning environments is analyzed. Based on the works of domestic and foreign scholars, the study reviews the potential of AI in systematizing knowledge, providing feedback mechanisms, and digitalizing the educational process through neural networks. Special emphasis is placed on the importance of cognitive styles in improving the efficiency of processing, analyzing, and applying knowledge.